MANAGEMENT PRECURSORS OF ENDOMETRIAL CANCER MAIN HOSPITAL SUPPORT "ALCIDE5 DANIEL CARRION" DURING THE YEARS 1980 – 1986 - Pacora, Luis (2015)
During the years 1980-1986, 2,428 uterine curettage Biopsy split in Gynecologic Oncology HPA-DAC was made. Retrospective study of 146 women carrying uterine bleeding is abnormal performs pre- and post-menopausal age, proceeding to rule out cervical neoplasia by clinical, cytology and histology, with the following results: proliferative endometrium 88 cases (60.27%); glandular cystic hyperplasia 24 cases (76.43%); adenomatous hyperplasia 15 cases (70.28%); atypical adenomatous hyperplasia 79 cases (13.02%). Major epidemiological history is analyzed, exposing the management carried out in these patients.